College, Interrupted: Profiles in First-Year College Students Responses to the COVID-19 Pandemic Across One Year. Issue 6 (December 2022) - Pasupathi, Monisha; Booker, Jordan; Ell, Mikayla; Follmer Greenhoot, Andrea; McLean, Kate C.; Wainryb, Cecilia; Fivush, Robyn
First-year college students in the 2019-2020 academic year are at risk of having their mental health, identity work, and college careers derailed as a result of the COVID-19 pandemic. To assess emerging and evolving impacts of the pandemic on mental health/well-being, identity development, and academic resilience, we collected data from a racially, ethnically, geographically, and economically diverse group of 629 students at four universities across the US within weeks of lockdown, and then followed up on these students' self-reported mental health, identity, and academic resilience three times over the following year. Our findings suggest that: 1) students' mental health, identity development, and academic resilience were largely negatively impacted compared to pre-pandemic samples; 2) these alterations persisted and, in some cases, worsened as the pandemic wore on; and 3) patterns of change were often worse for students indicating more baseline COVID-related stressors.